Performance evaluation of wireless multicarrier modem with DQPSK modulation for HF communications - Ahmad, Abdull Zubi (2005)
This thesis presents the bit error rate performances and throughput analysis over an HF radio channel using wireless multicarrier modem for voice and data services based on differential quaternary phase shift keying or DQPSK modulation in the presence of additive white Gaussian noise (AWGN) affected by slow Rayleigh fading. It combines two technologies – the highfrequency or HF band in the range of 3 – 30MHz to provide wireless long-distance and repeaterless communication links (eg. as used in the military) as well as multicarrier or parallel modem technology that provides simultaneous operations with the suppression of multipath components and other phenomena introduced by the ionosphere and also other narrowband interferences. In addition to conventional military applications for the fading radio channel, this implementation is also suitable for point-to-point links in the HF rural telecommunications area. The communications infrastructure for rural populations poses several problems which includes the generally long distances involved over which communication takes place as well as the low population densities which are also sparsely distributed. Thus, very expensive infrastructures like satellite links or long-haul repeater systems need to be employed which is aggravated by the fact that rural communities are in no position to pay for such facilities. A solution would thus require low cost wireless equipments incorporating HF and multicarrier technologies connecting the widely separated communities together as well as to the outside world. It is to be noted that multicarrier communication which employs HF radio technology will do away with third party equipments as well as the per-minute costs associated with satellite services